MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN DAYA NALAR MATEMATIKA SISWA MELALUI OPTIMALISASI PENGGUNAAN ALAT PERAGA - Maratun Nafiah; Ambar Rahmaningtyas (Perspektif Ilmu Pendidikan, 2009)
Many students of primary and secondary schools find matematics as a hard subject and are not strongly motivated to learn. Consequently their learning achievement is not as high as it is expected. This research attempted to find out the solution to this problem by using appropriate instructional media. The study was conducted in Government Primary School No 5 in Rawa Buaya, Cengkareng, West Jakarta. Research method usesd was Classroom Action Reasearch. which was implemented as from April through October 2009 in three cycles. After the third cycle the research discovered significant improvement in the studentsâ€™ motivation to learn mathematics and in their intellectual capability in doing mathematics. The reaserach concluded that the teacher can overcome the studentsâ€™ problems in learning mathematics particularly in srengthening their motivation and improving their entellectual skills in mathematics by using arppropiate madia. In doing so, the research gave a set of recommendations.